ANALYTICAL METHOD DEVELOPMENT, VALIDATION AND STABILITY STUDIES BY RP-HPLC METHOD FOR SIMULTANEOUS ESTIMATION OF ANDROGRAPHOLIDE AND CURCUMIN IN CO-ENCAPSULATED NANOSTRUCTURED LIPID CARRIER DRUG DELIVERY SYSTEM - DE, ASIT KUMAR; BERA, TANMOY (International Journal of Applied Pharmaceutics, 2021)
Objective: The current study aims to boost the bioavailability criteria of two natural bioactive compounds, andrographolide and curcumin by their combination in nanostructured lipid carrier (NLC) and also to develop a straightforward reverse-phase high-performance liquid chromatography (RP-HPLC) method to validate, quantify of andrographolide and curcumin simultaneously in novel NLC formulation. Methods: The reliable chromatographic separation was executed by using a column of Phenomenex octadecylsilane (C18) at 35 °C column oven temperature using a mobile phase of 0.02 M potassium dihydrogen orthophosphate (KH2PO4) salt solution of pH 3.0 as a buffer and acetonitrile in 50: 50 v/v fixed ratio and 1.5 ml/min flow rate of with 20 μl injection load. The detection was carried out at 240 nm isosbestic wavelength employing a photodiode array (PDA) detector. Results: Andrographolide and curcumin were eluted at 2.4 and 4.9 min, respectively. Quantification and linearity were achieved for both drugs at the 10-140 μg/ml range. The method is specified as the presence of excipients utilized in the formulation failed to interfere with the estimation of andrographolide and curcumin. The developed method was successfully utilized to work out the drug loading efficiency and in vitro drug release study of those drugs in NLC formulation and also for the estimation of those drugs from rat plasma. Conclusion: The developed high-performance liquid chromatography (HPLC) method may be utilized in the future estimation of andrographolide and curcumin simultaneously in NLC and other nanoformulations both in vitro and in vivo.